Qualitative composition of milk from Ukrainian Mountain Carpathian sheep - S. V. Chugaev; V. V. Fedorovych; Ye. I. Fedorovych (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
In recent years, the world, and Ukraine in particular, has seen a significant increase in consumer demand for sheep milk, as it has substantial advantages over cow's milk in terms of chemical composition and physical properties. Significant progress has been made recently in the study of the chemical composition of animal milk. However, most scientific papers are devoted to the study of bovine milk, and there is little data on sheep milk. In light of the above, the aim of our research was to study the chemical composition of milk from ewes of the Ukrainian Mountain Carpathian breed from the lowland (FG “Baikovo”, Khust district, Zakarpattia region) and mountainous (from the “Bansky” farm, Rakhiv district, Zakarpattia region) zones of the Carpathians. It was found that there was no significant difference in milk production between the ewes of both groups: their milk yield per lactation in the foothill zone was 75.5 kg, and in the mountainous zone, 79.5 kg. Additionally, the average duration of lactation, depending on the breeding zone, ranged from 193 to 197 days. The analysis of the chemical composition of the milk shows a significant intergroup differentiation in the studied traits. Thus, despite almost identical average daily milk yields, animals of the second group surpassed those of the first group by 3.61 (P < 0.001) in dry matter content, by 1.19 (P < 0.001) in protein content, by 1.86 (P < 0.001) in fat content, by 0.71 (P < 0.001) in lactose content, by 1.75 % (P < 0.05) in skimmed milk residue content, and by 208 kcal in caloric content. The acidity of the milk, depending on the breeding zone, ranged from 22.8 to 25.1 °T. Some multidirectional relationships were established between the average daily milk yield and the characteristics of the chemical composition of sheep milk, but none of them were significant. However, the most notable correlations were between average daily milk yield and dry matter content (0.27) and between average daily milk yield and skimmed milk solids (0.22). No consistent patterns were observed in relation to the animal breeding zones. In the intergroup differentiation of ewes of the Ukrainian Mountain Carpathian breed from the foothill and mountain zones based on the studied traits, the influence of the above factor on the phenotypic variability of lactation yield and average daily milk yield was insignificant, amounting to 1,8 % and 4,9 %, respectively. The influence of the breeding zone on the other studied traits of the chemical composition of sheep milk was more significant and statistically reliable, ranging, depending on the trait, from 17.7 % (P < 0.01) to 71.3 % (P < 0.001).